Optimization of hydrothermal performance in industrial heat sinks with innovative perforated pin fin designs: A numerical approach - Fatema-Tuj Zohora; Mohammad Rejaul Haque; Nabil Mohammad Chowdhury; Mostafa Kamal Fahad; Nowroze Farhan Ifraj (Heliyon)
This study emphasizes the importance of optimizing pin-finned heat sinks as a means of addressing thermal engineering issues. It aims to investigate the use of perforations and unique fin designs in relation to staggered pin arrays in order to fill a gap in existing research. Three-dimensional incompressible flow simulation is performed with the Fluent software. Modeling turbulence is accomplished by employing the realizable κ-ε models, while the numerical solution of all equations pertaining to fluid flow is carried out with the proper boundary conditions. In order to make a comparison of geometry, the hydrothermal performance factor (HTPF) is utilized for Reynolds number (Re) values ranging from 8500 to 44,502. Using a Re of 44502, the Nusselt number (Nu) was found to be raised by 66.2 % for spherical cube pin fins with hexagonal perforation and 70.2 % for elliptical perforation, respectively. A reduction of about 17.6 % in the pressure drop was seen when compared with an elliptical perforated infinity loop design, which resulted in a higher hydrothermal performance factor (HTPF) that was 70 % higher than that of the cylindrical case. Furthermore, the copper-diamond composite, which was placed on an infinity loop-shaped pin fin and had elliptical perforations, yielded a 144 % increase in HTPF when the Re is 44502. Taking into account this fact, it can be concluded that the designs that have been offered are ideal for a wide variety of industrial applications that aim to significantly enhance thermal potential.